2021
DOI: 10.33647/2074-5982-17-3-111-118
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Diethylbenzimidazolium Triodide in Pharmacotherapy of Chronic Compensated Tonsillopharyngitis

Abstract: The article presents the results of a clinical and bacteriological assessment of the pharmacological efficacy of 1,3-diethylbenzimidazolium triiodide in chronic compensated tonsillopharyngitis. As a result of a 10-day course of treatment, an improvement in the clinical status of patients was achieved, as well as a significant positive effect on the composition of the pharyngeal microbiocenosis. In particular, the content of Staphylococcus aureus, β-hemolytic streptococci, Escherichia signifi cantly decreased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To synthesize triiodides based on the thiohydantoin cation, we performed the reaction of compounds 3 a – c with elemental iodine in acetone. In the literature, the drugs based on the diethylbenzimidazolium triiodide salts are poorly described [33] although the combination of elemental iodine with organic component might extend the biological activity of the products. The triiodide salts 4 b,c were isolated in close to 90 % yield (Scheme 2), whereas triiodide salt 4a could not be isolated as an individual product but only as an inseparable mixture with the product of intramolecular cyclization 5 , as proved by the presence of the signals of the methylene groups at 4.82 ( 1 H) and 52.0 ppm ( 13 C) in 4 a and those at 7.43 ( 1 H) and 111.1 ppm ( 13 C) of the =CH group in the thiazole ring in 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To synthesize triiodides based on the thiohydantoin cation, we performed the reaction of compounds 3 a – c with elemental iodine in acetone. In the literature, the drugs based on the diethylbenzimidazolium triiodide salts are poorly described [33] although the combination of elemental iodine with organic component might extend the biological activity of the products. The triiodide salts 4 b,c were isolated in close to 90 % yield (Scheme 2), whereas triiodide salt 4a could not be isolated as an individual product but only as an inseparable mixture with the product of intramolecular cyclization 5 , as proved by the presence of the signals of the methylene groups at 4.82 ( 1 H) and 52.0 ppm ( 13 C) in 4 a and those at 7.43 ( 1 H) and 111.1 ppm ( 13 C) of the =CH group in the thiazole ring in 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The need for the salts of heterocyclic compounds is determined by the growing interest in these compounds due to wide application in different fields of science and technology. [32][33][34] With this in mind, the aim of the present work was to investigate the reactions of thiohydantoin with aliphatic, aromatic, and heteroaromatic α-iodoketones, and to explore the possibility of cyclization of the expected alkylation products. Earlier, we have shown that α-iodoketones, due to the high reactivity of the CÀ I bond, readily alkylate heterocyclic compounds with the carbonyl group in the molecule in the absence of bases or catalysts; the degree and regioselectivity of alkylation have also been investigated depending on the structure of the heterocycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation